2017
DOI: 10.1111/tbed.12638
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic characterization of porcine circovirus type 3 in China

Abstract: A novel circovirus called porcine circovirus type 3 (PCV3) was recently reported to exist in the USA. This circovirus is associated with porcine dermatitis, nephropathy syndrome and reproductive failure. This study reports on the first identification, widely epidemic, different phylogenetic clusters, potential role in sow reproductive failure and possible origins of PCV3 in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
239
6
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(265 citation statements)
references
References 19 publications
17
239
6
3
Order By: Relevance
“…All of these strains were grouped into PCV3 group 2, according to (Ku et al . ), and into group “a”, according to (Fux et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…All of these strains were grouped into PCV3 group 2, according to (Ku et al . ), and into group “a”, according to (Fux et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that PCV3 was detected in fetuses and it indicated that PCV3 could spread by vertical transmission (Ku et al . ). In this study, sequencing of the partials capsid gene revealed a high homology among the investigated strains and they also showed high homology with the fragment of CAP PCV3/29160.…”
Section: Discussionmentioning
confidence: 97%
“…The earliest case could be retrospective to the clinical sample collected in 2014 (Ku et al . ; Fan et al . ; Zheng et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PCV‐3 detection in the presence of different disease conditions such as porcine dermatitis and nephropathy syndrome, reproductive and respiratory disorders (Ku et al . ; Palinski et al . ; Shen et al .…”
Section: Introductionmentioning
confidence: 99%